2008
DOI: 10.1111/j.1744-7909.2008.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific Response of Photosynthesis to Burning and Nitrogen Fertilization

Abstract: The present study was conducted to examine photosynthetic characteristics of three dominant grass species (Agropyron cristatum, Leymus chinensis, and Cleistogenes squarrosa) and their responses to burning and nitrogen fertilization in a semiarid grassland in northern China. Photosynthetic rate (P(n)), stomatal conductance (g(s)), and water use efficiency (WUE) showed strong temporal variability over the growing season. C. squarrosa showed a significantly higher P(n) and WUE than A. cristatum and L. chinensis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…The decreased qCO 2 due to burning also reflects less water stress, which is contrary to the results of a previous study that burning induced higher qCO 2 because of exacerbated water stress (Graham and Haynes, 2006). Second, consistent with the studies in a Kansas tallgrass prairie (Ojima et al, 1994) and a mesic grassland (Heisler et al, 2004), greater solar radiation at the soil surface due to the removal of plant litter by burning can stimulate seed germination and photosynthesis (Zhang et al, 2008b), leading to enhanced plant growth and biomass in this experiment (Xu and Wan, 2008). Moreover, increased total respiration (Xu and Wan, 2008) in combination with decreased microbial respiration in the burned side (Fig.…”
Section: Burning Effectssupporting
confidence: 49%
See 1 more Smart Citation
“…The decreased qCO 2 due to burning also reflects less water stress, which is contrary to the results of a previous study that burning induced higher qCO 2 because of exacerbated water stress (Graham and Haynes, 2006). Second, consistent with the studies in a Kansas tallgrass prairie (Ojima et al, 1994) and a mesic grassland (Heisler et al, 2004), greater solar radiation at the soil surface due to the removal of plant litter by burning can stimulate seed germination and photosynthesis (Zhang et al, 2008b), leading to enhanced plant growth and biomass in this experiment (Xu and Wan, 2008). Moreover, increased total respiration (Xu and Wan, 2008) in combination with decreased microbial respiration in the burned side (Fig.…”
Section: Burning Effectssupporting
confidence: 49%
“…This study, as a part of a comprehensive research project in a temperate steppe in northern China since 2005 (Liu et al, 2007;Xu and Wan, 2008;Zhang et al, 2008b), was conducted to examine interannual variability of soil microorganisms in response to topography, burning, and N addition. The specific questions we would like to address include: (1) are there interannual differences in soil microbial biomass and respiration in response to topography, annual burning and N addition in this semiarid temperate steppe?…”
Section: Introductionmentioning
confidence: 99%
“…Although N is one of the most important factors controlling plant photosynthesis, the effects of N application on leaf‐level net assimilation rate are inconsistent. Nitrogen fertilization stimulated leaf photosynthesis in some cases (Mitchell and Hinckley 1993; Shangguan et al, 2000; Reich et al, 2003), but not in other cases (Lee et al, 2001; Martínez‐Carrasco et al, 2005; Niu et al, 2006; Zhang et al, 2008). A previous study of L. chinensis in the same geographic area also showed that N fertilization had no effect or even a tendency of a negative effect on photosynthesis (Niu et al, 2006; Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…However, little is known about the interaction between the key regulators (precipitation and nitrogen) and the effect of grazing. In several studies the effect of water (van Staalduinen and Anten 2005;Zhao et al 2008), nitrogen (Chen et al 2005;Zhang et al 2008) or grazing (Liang et al 2002;Liang et al 2009;Xie and Wittig 2003) on different steppe grass species has been analysed, predominantly in pot experiments. Therefore, the present study was conducted to interactively analyse effects of grazing, water and nitrogen on major C3 and C4 grass species.…”
Section: Introductionmentioning
confidence: 99%